2002
DOI: 10.1074/jbc.m202345200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Polymorphic CYP3A7 Expression in Adult Human Liver and Intestine

Abstract: Human CYP3A enzymes play a pivotal role in the metabolism of many drugs, and the variability of their expression among individuals may have a strong impact on the efficacy of drug treatment. However, the individual contributions of the four CYP3A genes to total CYP3A activity remain unclear. To elucidate the role of CYP3A7, we have studied its expression in human liver and intestine. In both organs, expression of CYP3A7 mRNA was polymorphic. The recently identified CYP3A7*1C allele was a consistent marker of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
145
1
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(153 citation statements)
references
References 31 publications
4
145
1
3
Order By: Relevance
“…Its expression level decreases rapidly after birth and becomes undetectable in most adult livers, except for the subjects carrying one of two promoter variants, CYP3A7*1B and CYP3A7*1C. [6] CYP3A43 is also expressed at very low levels in adult livers, accounting for only 0.1-0.2% of CYP3A transcripts. [7,8] Interestingly, the hepatic expression of CYP3A5 is bimodal, with the high expressor exhibiting 10-30 fold higher CYP3A5 expression levels than the CYP3A5 lower expressor.…”
Section: Introductionmentioning
confidence: 99%
“…Its expression level decreases rapidly after birth and becomes undetectable in most adult livers, except for the subjects carrying one of two promoter variants, CYP3A7*1B and CYP3A7*1C. [6] CYP3A43 is also expressed at very low levels in adult livers, accounting for only 0.1-0.2% of CYP3A transcripts. [7,8] Interestingly, the hepatic expression of CYP3A5 is bimodal, with the high expressor exhibiting 10-30 fold higher CYP3A5 expression levels than the CYP3A5 lower expressor.…”
Section: Introductionmentioning
confidence: 99%
“…3 The contribution of CYP3A43 and CYP3A7 to the metabolism of CYP3A substrates in adults is therefore thought to be negligible. 1,3 The total CYP3A catalytic activity is thus mainly because of CYP3A4 and CYP3A5.…”
Section: Introductionmentioning
confidence: 99%
“…3 The contribution of CYP3A43 and CYP3A7 to the metabolism of CYP3A substrates in adults is therefore thought to be negligible. 1,3 The total CYP3A catalytic activity is thus mainly because of CYP3A4 and CYP3A5. 4 Most substrates for CYP3A4 are also metabolized by CYP3A5, although the relative contribution of CYP3A5 to CYP3A-mediated metabolism may differ for different substrates.…”
Section: Introductionmentioning
confidence: 99%
“…2006;Bluth MH, 2011) [ Table 4]. A number of studies have shown interindividual variability and tissue specificity in the expression of cytochrome P450 gene expression (Koch I, et al, 2002). As a result, patients can be classified into four phenotypes based on the level of a CYP enzyme activity: poor metabolizer (abolished activity), intermediate metabolizer (reduced activity), extensive metabolizer (normal activity), and ultrarapid metabolizer (enhanced activity).…”
Section: Polymorphisms In the Cyp-450 Genesmentioning
confidence: 99%